2020
DOI: 10.1016/j.trc.2020.102816
|View full text |Cite
|
Sign up to set email alerts
|

Cooperate or not? Exploring drivers’ interactions and response times to a lane-changing request in a connected environment

Abstract: Lane-changing is one of the complex driving tasks that depends on the number of vehicles, objectives, and lanes. A driver often needs to respond to a lane-changing request of a lane-changer, which is a function of their personality traits and the current driving conditions. A connected environment is expected to assist during the lane-changing decision-making process by increasing situational awareness of surrounding traffic through vehicle-to-vehicle communication and vehicle-to-infrastructure communication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 102 publications
1
12
0
Order By: Relevance
“…Ali et al [14] used a parametric accelerated failure time hazard-based duration model to study the minimum gap time between the interacting vehicles during the mandatory lane-changing. Duration is another important characteristic of lane-changing behavior [15][16][17]. Studies have demonstrated that the duration of a lane change roughly ranges from 0.5 s to 16 s and obeys a normal distribution [18].…”
Section: Characteristics Of Lane Change In Highway Diversionmentioning
confidence: 99%
“…Ali et al [14] used a parametric accelerated failure time hazard-based duration model to study the minimum gap time between the interacting vehicles during the mandatory lane-changing. Duration is another important characteristic of lane-changing behavior [15][16][17]. Studies have demonstrated that the duration of a lane change roughly ranges from 0.5 s to 16 s and obeys a normal distribution [18].…”
Section: Characteristics Of Lane Change In Highway Diversionmentioning
confidence: 99%
“…Additionally, drivers' response times are modeled using a random parameter accelerated failure time (AFT) hazardbased duration model. Results revealed that drivers tend to be more cooperative in response to a lane-changing request in the connected environment compared with the baseline condition whereby they tend to accelerate to avoid the lanechanging request [25]. Hence, a large number of works were conducted to focus on the two-dimensional prediction of trajectories for the driving behavior mimicking of humans [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…e autonomous vehicle (AV) is able to detect its surroundings, identify obstacle, and signages that, in turn, enable it to develop its navigation paths and move along the road network without human control. Current AV research projects have focused on developing AV technologies to improve vehicle safety, particularly when performing its fundamental tasks, including car following, lane-keeping, and lane-changing [1][2][3][4][5][6]. Due to its complex process, which involves interactions of host vehicles and its following and leading vehicles, little attention has been given to the AV lane change prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its complex process, which involves interactions of host vehicles and its following and leading vehicles, little attention has been given to the AV lane change prediction model. e existing lane-change algorithm (e.g., trajectory planning and maneuver planning algorithm) focused on maximizing individual vehicles' benefit [1][2][3][4][5][6]. In addition to that, these algorithms required detailed microscopic traffic variables (i.e., relative speed and positions) of the surrounding subject vehicles, gaps between the host and following and leading vehicles, which often depends not only on the behavior and movement of the surrounding vehicles but also on the macroscopic traffic dynamics.…”
Section: Introductionmentioning
confidence: 99%